Effect of successive subculture of Cordyceps militaris on growth, metabolites production and stability of Rhf1 gene - ChokeUmnuay, Nut; Owatworakit, Amorn (Agriculture and Natural Resources, 2021)
Degeneration of Cordyceps militaris has been progressively studied because it is a highly valued fungus with strong market demand. The current study investigated mycelial growth, metabolite (adenosine and cordycepin) production and variations in the Rhf1 gene (filamentous protein) during successive subcultures for five generations (G1–G5). The results indicated that the mycelial growth rate and biomass were initially consistent during G1–G2 and the degeneration initiated at G3 progressed until G5. The decrease was 22% (from 0.35 ± 0.01 cm/d to 0.27 ± 0.02 cm/d) and 42% (from 0.95 ± 0.04 g dry weight (DW) and 0.55 ± 0.01 g DW), respectively. There was a significant reduction in the adenosine and cordycepin production in G1 (1.97 ± 0.02 μg/g DW and 5.49 ± 0.11 μg/g DW) compared with G5 (0.03 ± 0.001 μg/g DW and 1.63 ± 0.02 μg/g DW), which was much for adenosine than cordycepin. Next, the gene copy number and gene expression of the Rhf1 gene were compared among the five generations using quantitative real-time polymerase chain reaction, revealing that it significantly (p < 0.05) decreased after G3 compared to G1. Consistently, the percentage of DNA methylation of Rhf1 was greater in G3 (more than 50% compared to G1). These results suggested that methylation may be associated with the stability of the Rhf1 gene during subculture degeneration, thereby affecting Rhf1 gene expression. Hence, the number of Rhf1 gene copies may be useful in the determination of the quality of C. militaris before cultivation.